Changes in the Expression Profile of JAK/STAT Signaling Pathway Genes and Mirnas Regulating their Expression Under the Adalimumab Therapy - Grabarek, Beniamin; Wcislo-Dziadecka, Dominika; Gola, Joanna; Kruszniewska-Rajs, Celina; Brzezinska-Wcislo, Ligia; Zmarzly, Nikola; Mazurek, Urszula (Current Pharmaceutical Biotechnology, 2018)
Objective: The aim of this study was to evaluate the influence of adalimumab on the expression pattern of genes associated with JAK/STAT signaling pathway in Normal Human Dermal Fibroblast (NHDF) cells stimulated with 8 μg/ml of adalimumab and the identification of miRNAs regulating these genes’ expression. Method: NHDFs were cultured with or without the presence of adalimumab for 2, 8, and 24h. The microarray technology was used to determine expression profile of mRNAs and miRNAs. Results: Out of 22283 ID mRNA, 37 are associated with the JAK/STAT signaling pathway. It can be observed that 18 mRNAs differentiate NHDFs cultures with adalimumab from control. The analysis of miRNAs showed that, among 1105 ID miRNAs, 20 miRNAs are differentiating in cells treated with adalimumab for 2h, 9 miRNAs after 8h, and only 3 miRNAs after 24h. Conclusion: It can be observed that miRNAs play an extremely important role in the regulation of the expression of genes associated with JAK/STAT signaling pathway. The results of this study show the possibility of using changes in mRNAs and miRNAs profile expression, as complementary molecular markers of adalimumab treatment effectiveness.
Keywords: JAK/STAT signaling pathway